A proposed model of temporal cash waqf account: a maqasid approach - Ghalia, Bouhedda; Kassim Wan Mohd., Salina; Jawwad, Ali (2021)
: Waqf is an Islamic socio-economic sector that combines both the worldly interests and an ongoing reward (Ṣadaqah Jāriyah) in the hereafter. Moreover, there is an increasingly dire need among Muslims to cooperate and extend solidarity in all aspects of goodness, including the institution of Waqf. This is also important in the context of emergency conditions like Covid-19 and its economic effects on societies leading to increasing unemployment, poverty due to bankruptcy, and lockdown that has paralyzed many economic sectors. In fact, activating the temporal and Cash Waqf would lead to facilitate and encourage Muslims to endow their money: usufruct and cash frequently. To achieve this objective, there is a need to organize this type of Waqf from both Maqasidic and administrative perspectives. This paper attempts to present a proposed model of combined cash and temporal Waqf for the governance, in which both cash and temporal Waqf would be discussed from theory to the practices. This study adopts inductive and analytical approaches in qualitative research to accomplish its objective. The study also, conducts field research to explore the opinions of Waqf experts in Malaysia through online interviews. This study would result that the combine model of cash and temporal Waqf can play a crucial role in poverty alleviation, and quality education, which are among the Sustainable Development Goals (SDG).